PRESENTASI DIRI BUJANG DAN DARA RIAU TAHUN 2013 - Ramadhani Alberni; Welly Wirman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Self presentation is usually done by people with certain professions who are required to have a positive self-image, including Bujang and Dara Riau. Although derived from the ethnic Malay, Bujang and Dara Riau must be able to perform as Tourism Ambassadors who carry out their duties in open, friendly, responsible, and courteous. In other words, when performing in front stage as Bujang and Dara Riau, both have an identity and self-presentation whose are different when in the back stage just like other social beings. Both stages is known as Dramaturgy. This study aim to learn the life in front stage and back stage of Bujang and Dara Riau 2013 as the Riau province of Indonesia Tourism Ambassador and Riau province of Indonesia Miss Tourism.This study use qualitative research methods with phenomenological approach and data collection techniques that are grouped through participant observation, in-depth interviews, and documentation. This study use Miles and Hubermen’s interactive Data Analysis model, using examination technique of data validation through extension of participation and triangulation.Results of this study shows; front stage’s life of Bujang and Dara Riau 2013 is that always feel pleased and proud in their duties which appeared wearing traditional dress or formal dress which wrapped with a cloth sling, along with smile to guest. Back stage’s life of Bujang and Dara Riau 2013 did not have any demands, they can act with their own style when they with close friends and also doesn' want status and fabric sling change their nature and character. Self Presentation of Bujang and Dara Riau 2013 can be a figure with hospitability and not to show off when being in front stage with self presentation also a demand from tasks and status as Bujang and Dara Riau 2013. Summary of front stage’s life from interviewees with status as Bujang and Dara Riau 2013 is a process of image’s management which done in order to meet the expectations, demands and existence. Back stage’s life of interviewees as